All the World’s a Game: Video Game Culture and the Videoludification of Society (KULT_online, 2019)
In Video Games as Culture: Considering the Role and Importance of Video Games in Contemporary Society, sociologists Daniel Muriel and Garry Crawford set out to explore the growing video game culture that has become part and parcel of our everyday life. Drawing on qualitative ethnographic research, the authors offer a pioneering study of the actors, practices, meanings, and identities associated with games and gaming. Connecting game culture to 21st century challenges and transformations such as digitalization and neoliberal culture, Video Games as Culture is an inspiring approach to understanding the world we live in that will appeal to students and professionals alike.